Tailored heat treated blanks applied on car body parts under quasi-series conditions. (15th February 2010) - Merklein, M.; Geiger, M.; Staud, D.; Vogt, U.
The soaring pursuit for weight reduction of car body parts originates from the need for efficient fuel consumption and for reduced CO2-emissions, respectively. Aluminium alloys qualify for light weight constructions due to their low density at comparatively high strength. The formability of aluminium alloys, however, is relatively poor. In this respect, innovative technologies for aluminium sheet forming have to be developed. In this paper, the application of tailored heat treated blanks (THTB) for fast hardenable aluminium alloys of the 6000-series is presented. THTB are locally heat treated aluminium blanks exhibiting a specific strength pattern optimised to the forming operation. Based on material and lubricant related investigations, process boundaries for the THTB design are derived. Moreover, to identify the most appropriate strength distribution and so the relevant heat treatment parameters of a THTB, an inverse, FE-based approach for the design of THTB allowing effective and efficient THTB engineering cycles is introduced.